GARNET PORPHYROBLAST TIMING AND BEHAVIOUR DURING FOLD EVOLUTION: IMPLICATIONS FROM A 3-D GEOMETRIC ANALYSIS OF A HAND-SAMPLE SCALE FOLD IN A SCHIST - Timms N.E. (My University, 2003)
Detailed 3-D analysis of inclusion trails in garnet porphyroblasts and matrix foliations preserved around a hand-sample scale, tight, upright fold has revealed a complex deformation history. The fold, dominated by interlayered quartz-mica schist and quartz-rich veins, preserves a crenulation cleavage that has a synthetic bulk shear sense to that of the macroscopic fold and transects the axis in mica-rich layers. Garnet porphyroblasts with asymmetric inclusion trails occur on both limbs of the fold and display two stages of growth shown by textural discontinuities. Garnet porphyroblast cores and rims pre-date the macroscopic fold and preserve successive foliation inflection/intersection axes (FIAs), which have the same trend but opposing plunges on each limb of the fold, and trend NNE-SSW and NE-SW, respectively. The FIAs are oblique to the main fold, which plunges gently to the WSW. Inclusion trail surfaces in the cores of idioblastic porphyroblasts within mica-rich layers define an apparent fold with an axis oblique to the macroscopic fold axis by 32°, whereas equivalent surfaces in tabular garnet adjacent to quartz-rich layers define a tighter apparent fold with an axis oblique to the main fold axis by 17°. This potentially could be explained by garnet porphyroblasts that grew over a pre-existing gentle fold and did not rotate during fold formation, but is more easily explained by rotation of the porphyroblasts during folding. Tabular porphyroblasts adjacent to quartz-rich layers rotated more relative to the fold axis than those within mica-rich layers due to less effective deformation partitioning around the porphyroblasts and through quartz-rich layers. This work highlights the importance of 3-D geometry and relative timing relationships in studies of inclusion trails in porphyroblasts and microstructures in the matrix.
Keywords: DEFORMATION PARTITIONING; INCLUSION TRAILS; ROTATION AXIS